124k views
5 votes
How would you solve 8(6-k)+2k ≥-15-(-3k) ( please show each step)

2 Answers

2 votes

Answer:

k ≤ 7

Explanation:

8 (6 - k) + 2k ≥ - 15 -(-3k)

Let's simplify this by solving each side.

First side:

8 (6 - k) + 2k ≥ - 15 -(-3k)

48 - 8k + 2k ≥ - 15 -(-3k)

48 - 6k ≥ - 15 -(-3k)

Second side:

48 - 6k ≥ - 15 -(-3k)

48 - 6k ≥ -15 + 3k

DONE SIMPLIFYING!

Now solve for "k" algebraically (transitions are in bold):

48 - 6k ≥ -15 + 3k

-6k ≥ -15 - 48 + 3k

-6k ≥ -63 + 3k

-6k - 3k ≥ -63

-9k ≥ -63

-k ≥ -63 ÷ 9

-k ≥ -7

k ≤ 7

6 votes

Answer:

Explanation:

8(6-k)+2k ≥-15-(-3k)

Opening bracket

48 - 8k + 2k ≥ -15 + 3k

-8k - 3k + 2k ≥ -15 - 48

-9k ≥ -63

k ≤ -63/-9

k ≤ 7

User Bao Nguyen
by
5.3k points